2018
DOI: 10.3390/ijerph16010089
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Commuting: Ignoring Individuals’ Activity-Travel Patterns May Lead to Inaccurate Assessments of Their Exposure to Traffic Congestion

Abstract: This research examines whether individual exposures to traffic congestion are significantly different between assessments obtained with and without considering individuals’ activity-travel patterns in addition to commuting trips. We used crowdsourced real-time traffic congestion data and the activity-travel data of 250 individuals in Los Angeles to compare these two assessments of individual exposures to traffic congestion. The results revealed that individual exposures to traffic congestion are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…In recent years, researchers have become aware of this measurement bias in greenspace exposure [20,21], traffic exposure [22,23], environmental impacts on mental health and substance use [24][25][26], exposure and risk misclassification in epidemiological studies [27]. Furthermore, static measurements based on people's residential neighborhoods also seem problematic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers have become aware of this measurement bias in greenspace exposure [20,21], traffic exposure [22,23], environmental impacts on mental health and substance use [24][25][26], exposure and risk misclassification in epidemiological studies [27]. Furthermore, static measurements based on people's residential neighborhoods also seem problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Kwan found that the UGCoP and the NEAP exist and may affect the results of traffic congestion exposure assessments. They argued that mobility-based exposure measures would be more accurate because they also capture individuals' exposures in areas outside their residential neighborhoods [22]. Some scholars have started to measure environmental exposure while taking into account individuals' daily mobility and travel routes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advances in geospatial technologies and GIScience methods have allowed researchers to analyze and visualize geospatial data in great detail (Gutmann et al, 2008;Kwan, 2012;Richardson et al, 2013). For instance, maps have been widely utilized to visualize the complex patterns of diverse social phenomena, such as infectious diseases and human daily mobility (e.g., Kim & Kwan, 2019Kim & Lee, 2019;Kwan, 2004;Reich & Haran, 2018). At the same time, however, mapping people's confidential geospatial data (e.g., people's homes, workplaces, or GPS trajectories) may allow an individual's identity (e.g., name and street address) to be identified from a map (A.J.…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that if people's daily activities are ignored, mobility-dependent exposures could be overestimated for people with high residence-based exposures and underestimated for people with low residence-based exposures. Since its articulation in 2018, there are only a few empirical studies on the NEAP, and all of these studies focused on individual exposure to air pollution [9][10][11]. More empirical evidence on the NEAP based on examining other types of mobility-dependent exposures is thus sorely needed.…”
Section: Introductionmentioning
confidence: 99%